Capital Structure and Financial Performance of Manufacturing Companies in Nepal - Lamichhane, Pitambar; Dhungel, Bashu Dev (MASI Mandiri Edukasi, 2024)
In the present competitive globalized business environment, capital structure is a debatable issue in finance, and how firms mix debt and equity to minimize the cost of capital to accelerate firms’ financial performance. Financial performance is influenced by various factors, and capital structure is one of the key factors. Therefore, this study intends to investigate how capital structure (CS) influences financial performance measured by the return on capital (ROC) and net profit margin (NPM) of manufacturing companies in Nepal. This paper employs descriptive and causal research designs to examine the impact of CS on financial performance in Nepalese manufacturing companies. The correlation result explores the positive relation of financial performance with debt to common equity. An inverse association is observed with debt to assets, long-term debt to equity, and long-term debt to capital ratios. The regression result reveals that more debt to equity-capital plays a significant positive role in enhancing financial performance measures such as return on capital employed and net profit margin. Regression results conclude that higher utilization of debt to assets, long-term debt-equity, and long-term debts to capital adversely affect financial performance. Therefore, Nepalese manufacturing companies should manage and control the utilization of their long-term debt to maintain optimal capital structure, which enhances maximizing their financial performance. The implication of this paper is for policymakers, executives, regulatory bodies, and academics to make decisions about capital structure and financial performance in Nepal.